Al-Muhkam Wal-Mutasyabih - T, Tawarati; Ondeng, Syarifuddin (Penerbit Yayasan Daarul Huda Kruengmane, 2025)
This article not only serves as a theoretical exploration of the concept of AlMuhkam wal-Mutasyabih, but also attempts to provide a practical contribution. By understanding these two characteristics of verses in the Qur'an, Muslims can reflect on religious teachings in more depth, using this concept as a guide in dealing with various aspects of daily life. In the series of thoughts about Al-Muhkam wal-Mutasyabih, we find not only theological wisdom, but also practical guidance for Muslims. This concept enriches our understanding of the Qur'an, inviting us to reflect on its deep meanings. By deepening our understanding of Al-Muhkam wal-Mutasyabih, we can live. This study uses a qualitative descriptive approach with the main data from library data. The collected data was analyzed using qualitative analysis starting from data coding, data reduction and drawing conclusions. The results of the study show that in the muhkam and mutasyabih verses contained in the Koran there are quite diverse differences of opinion regarding the meaning of the terms of these two verses, as there are many differences in determining the criteria for determining which verses are considered muhkamat and which verses are mutasyabihat. The mutasyabihat verse basically requires interpretation/explanation due to the vague meaning contained in it. That is why efforts to interpret the mutasyabihat verse to a meaning that is in accordance with the rule.